Modern Methods of Creative Development of the Child in Preschool Education (Eurasian Research Bulletin, 2022)
Different factors affect the formation of the scientific worldview of children in different ways. Among these factors, the most important is the development of creative and mathematical thinking. After all, the process of forming imagination and concepts in a child begins in preschool, and this period is the most important stage in the content of the formation of a worldview. Therefore, the preschool period is a key period in the formation of concepts and representations.